Cultural Heritage’s Value in African Sustainable Development - (:unkn) unknown (My University, 2022)
Over the past half century, our understanding of development has shifted from economic growth to economic viable, social equitable, and environmental bearable, so-called “sustainable development”. The United Nations (UN) has launched 17 sustainable development goals (SDGs) by 2030 (UN 2015), three of which relate to sustainable tourism. The latter is not a new category of tourism but a new ethic to guide tourism. World Heritage, including Cultural Heritage, Natural Heritage, and Mixed Heritage, especially Cultural and Mixed heritage properties, link closely with local communities’ development and become tourist attractions with physical stability, historical continuity, archeological authenticity or aesthetic harmony. Cultural Heritage begins with capital letters in this paper indicating it as the United Nations Educational, Scientific and Cultural Organization (UNESCO) World Heritage.The chapter introduces: 1) - an overview of Africa’s Cultural Heritage; 2) - explains why Africa’s Cultural Heritage is significant for sustainable development from a theoretical perspective, based on relevant UN documents; 3) – highlights the challenges faced by all stakeholders: African governments, local communities, tourist agencies, national and international visitors, etc., on how to enhance the value of Africa’s Cultural Heritage through tourism; 4) - analyzes potential value of Africa’s Cultural Heritage, as a driver and resource for sustainable development; and finally, 5) – concludes with the economic, social, and environmental value of Cultural Heritage in African sustainable development.
Keywords: African Research